2022
DOI: 10.12659/msm.937784
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Serum Levels of 5 Amino Acids and Dimethylamine Using Liquid Chromatography-Tandem Mass Spectrometry in Patients without Septic Associated Acute Kidney Injury and with Septic Associated Acute Kidney Injury Requiring Continuous Renal Replacement Therapy

Abstract: Background Acute kidney injury (AKI) is one of the most common organ failures. An early diagnosis of AKI using specific biomarkers is essential for effective treatment. This study determined the serum concentrations of selected amino acids and amines using targeted liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) in patients with AKI during sepsis and septic shock treated in the Intensive Care Unit (ICU). Material/Methods A sample of 41 patients wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some may roughly reflect the magnitude of the organ pathology—for example, liver injury (increasing transaminases levels), liver dysfunction (e.g., modestly increased bilirubin levels), liver failure (high bilirubin, profound coagulopathy), but there are, admittedly, many confounders. Human studies have demonstrated alterations in levels of numerous biomarkers in sepsis, and their correlation with organ failure and mortality, including markers of endothelial activation and injury, long noncoding RNAs, cancer protein biomarkers, and brain natriuretic peptide (64–68). Markers of leukocyte activation and function also associate with sepsis outcomes (67, 69–72).…”
Section: Resultsmentioning
confidence: 99%
“…Some may roughly reflect the magnitude of the organ pathology—for example, liver injury (increasing transaminases levels), liver dysfunction (e.g., modestly increased bilirubin levels), liver failure (high bilirubin, profound coagulopathy), but there are, admittedly, many confounders. Human studies have demonstrated alterations in levels of numerous biomarkers in sepsis, and their correlation with organ failure and mortality, including markers of endothelial activation and injury, long noncoding RNAs, cancer protein biomarkers, and brain natriuretic peptide (64–68). Markers of leukocyte activation and function also associate with sepsis outcomes (67, 69–72).…”
Section: Resultsmentioning
confidence: 99%
“…As anticipated, sepsis patients displayed decreased levels of glutamate, leucine, phenylalanine, tryptophan and tyrosine [ 5 ]. Serum dimethylamine concentrations were found to be elevated in septic shock patients with acute kidney injury by targeted liquid chromatography-tandem mass spectrometry [ 11 ].…”
Section: Discussionmentioning
confidence: 99%